EFFICACY OF PGF 2~, CIDR AND OVSYNCH, TREATMENT ON ESTRUS RESPONSE AND FERTILITY RATE IN CROSSBRED COWS - SATHIAMOORTHY, T; KATHIRCHELVAN, M (The Indian Journal of Animal Reproduction, 2023)
A total of three hundred and seventy five postpartum crossbred cows were divided into three groups vizgroup I, II and Ill. Group I animals (n=180) were treated with PGF2" after palpation of corpus llJteum. Group IIanimals (n=155) were treated with CIDR (Controlled Internal Drug Release Device). Group Ill animals (n=40) weretreated with ovsynch protocol. Fixed time artificial insemination was performed in the responded animals. Percentageof induced estrus and mean onset of induced estrus were 71.11, 83.20, and 67.50 and 58.8, 44.4, 53.4 hrs in groupI, ti and Ill respectively. First service conception rate was 52.20, 42.74 and 55.55 per cent in group I, II and Illrespectively. From this study it may be concluded that Ovsynch treated crossbred cows gave better fertility ratecompared to PGF2a and CIDR treated cows.
Keywords: Ovsynch protocol; Fertility rate; Cows